Estudo do transporte eletrônico de uma junção P-i-N com poço quântico único de GaAs - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
In this work the electrical properties of devices with double potential barrier studied both theoretically and experimentally. For the experimental analysis was made a sample P-i-N with two AlAs potential barriers with a width of 200A and between quantum well of 100A wide GaAs, the device was grown by MBE (Molecular Beam Eptaxy). First and made a theoretical approach to semiconductor heterostructures composed of quantum wells. To place the electronic transport the device is required deposition of metal contacts on the device surface, so it was made a study of the behavior in the semiconductor interface when and inserted a metal, addressing current transport phenomena and the types of contacts formed (Schottky or ohmic). To characterize the resistance and resistivity of the contacts has been studied and applied the method TLM (Transmission Line Model) , showing that the contact made in the sample P N is of the type ohmic. Subsequently to the diode resonant tunneling, theoretical models for the transport of tunneling current were discussed, showing the exact calculation of the probability of tunneling of electrons through the system. In this case, it took into consideration the Schrodinger equation the external voltage, showing that the wave functions in the barriers and quantum well has the analytical solution, the linear combination of Airy functions. Finally, the transmissivity was obtained using the formalism of the transfer ma-trix method, so it was developed an algorithm in Maple15® program that calculates T transmission coefficient, from these results it was possible to transmissibility curves as a function of the energy of the incident electron and curves of the tunneling current density according to the external voltage. These results were compared with those of literatures and the experimental result of the sample curve ixV P-i-N. Finally, a new sample morpho-logy was proposed for future work.
Keywords: Heteroestrutura; Poço Quântico; Tunelamento; Contato Ôhmico; Transmissividade; CIÊNCIAS EXATAS E DA TERRA: FÍSICA